Comparative Effects of Resistance Training Modalities on Mental Health and Quality of Life in Individuals with Spinal Cord Injury - Lucas Vieira Santos; Karla Raphaela da Silva Ramos Freitas; Eveline Torres Pereira; Luciano Bernardes Leite; Pedro Forte; Claudia Eliza Patrocínio de Oliveira; Osvaldo Costa Moreira (Sports)
Background: Anxiety and depression are prevalent after spinal cord injury, impairing social participation and quality of life. Objective: This study aimed to investigate the effects of traditional resistance training (TRT), flywheel resistance training (FWRT), and high-velocity resistance training (HVRT) on the mental health and quality of life in individuals with spinal cord injury. Methods: Thirty-two participants were divided into TRT (n = 12), FWRT (n = 8), and HVRT (n = 12) groups, undergoing 8 weeks of upper-limb training twice weekly under super-vision. Training intensity and volume were progressively increased. The Hospital Anxiety and Depression Scale and SF-36 Questionnaire were used to assess outcomes. Results: Both the TRT and FWRT groups showed a reduction in HADS-D scores post-intervention (p < 0.001). The TRT group also presented a significant reduction in HADS-A scores post-intervention (p = 0.003). Concerning quality of life, after training, TRT showed improvements in social functioning (p = 0.013), FWRT improved scores in physical functioning (p = 0.002), bodily pain (p = 0.002), vitality (p = 0.046), and role emotional (p < 0.001), while HVRT enhanced role physical (p < 0.001), social functioning (p = 0.013), and role emotional (p < 0.001). Conclusion: Overall, TRT was the most effective in reducing anxiety and depression and enhancing quality of life, while FWRT showed notable gains in physical and functional capacity. HVRT demonstrated improvements primarily in role physical but was less effective in other domains.